The Influence of Participatory Technology and Institutional Participation of Farmer Groups on Farmer Business Development: Pengaruh Teknologi Partisipatif dan Partisipasi Kelembagaan Kelompok Tani Terhadap Pengembangan Usaha Tani - Romadi , Ugik; Gunawan , Gunawan; Mohammad , Falah Haris (Jurnal Penyuluhan, 2023)
Janti Village, Jogoroto, Jombang has a corn productivity of 2020 reaching 84.5 Kw/Ha, this achievement exceeds national average corn productivity. However, this is inversely proportional to the unstable price of corn, which can even be far from the normal price. Besides, the lack of farmer participation makes the problem drag on longer. The existence of farmer group institutions is very important to solve this problem. In addition, the application of participatory technology to farmers also provides clear goals for future agricultural production activities. Therefore, it is necessary to be active and participate in the Janti Village farmer group members. The purpose of this study is to describe the influence of participatory technology (discussions, workshops, and action planning) and institutional participation of farmer groups (participation in planning, implementation, utilization of results, and evaluation) on farming development (social, economic, and environmental) in Janti Village. Jogoroto District, Jombang Regency. The research method uses descriptive quantitative data collection techniques namely interviews, observation, and questionnaires. Previously, the questionnaire had to be tested for validity and reliability tests to support the validity of the research data obtained. The sampling method used is a simple random sample. Then the data analysis used is multiple linear regression analysis using the ordinary least square method including data tabulation, estimation of multiple linear regression models, classical assumption tests, regression feasibility tests, and interpretation of multiple linear regression models. Results showed that there was no significant effect if independent variables moved independently on dependent variables. Meanwhile, if independent variables move simultaneously, there will be a significant influence between participatory technology and the institutional participation of farmer groups in the development of farming businesses.